Fast-killing parasites can be favoured in spatially structured populations. (5th May 2017) - Leggett, Helen C.; Wild, Geoff; West, Stuart A.; Buckling, Angus
Abstract : It is becoming increasingly clear that the evolution of infectious disease is influenced by host population structure. Theory predicts that parasites should be more 'prudent'—less transmissible—in spatially structured host populations. However, here we (i) highlight how low transmission, the phenotype being selected for in this in context, may also be achieved by rapacious host exploitation, if fast host exploitation confers a local, within-host competitive advantage and (ii) test this novel concept in a bacteria–virus system. We found that limited host availability and, to a lesser extent, low relatedness favour faster-killing parasites with reduced transmission. By contrast, high host availability and high relatedness favour slower-killing, more transmissible parasites. Our results suggest high, rather than low, virulence may be selected in spatially structured host–parasite communities where local competition and hence selection for a within-host fitness advantage is high. This article is part of the themed issue 'Opening the black box: re-examining the ecology and evolution of parasite transmission'.